Impact of Technological Advancements on The Establishment of Characteristics of Children - Imam Tabroni; Hasna Husniyah; Lusi Sapitri; Yunisa Azzahra (East Asian Journal of Multidisciplinary Research, 2022)
The progress of information systems and technology today is indeed so rapid. This of course has an impact on various orders of life, including the characteristics of a child. In completing this research, the researcher used research methods with qualitative and quantitative approaches. In the process of finding information the researcher uses the method; Observation, and study of literature from various sources such as scientific journals and books. This study analyzes the impact of technological advances on the formation of children's character. As for the results, most children have characteristics that are not good. In addition, technology has a good side, especially in terms of learning, namely it can create effectiveness in learning. However, the use of gadgets outside of class hours needs to be a concern for educators, especially parents.